PERANCANGAN TRAFFIC LIGHT BERBASIS MICROCONTROLLER ATMEGA 16 - Alfith Alfith (ITP Press)
Today, the highway as a means to facilitate transport often have problems, caused by all road users desire more quickly to the destination, and precede each other, plus more if there is a special car or a group, it is very influential on the impact on the density of traffic congestion . To address them, in fact is not the duty of the police to regulate the traffic, but we can help to regulate traffic in any place such as a T-junction, intersection, or perlimaan densely trafficked rate traffic arrangements necessary tool called the Traffic Light. This is the basis for